2005
DOI: 10.1093/hsw/30.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Long-Term Prostate Cancer Survival: The Perspective of Elderly Asian/Pacific Islander Wives

Abstract: Increasingly evident is the important role of partners in patients' adaptation to diagnosis, treatment, and recovery. Yet, little is known about partners' adaptation when patients reach the benchmark known as long-term survival. This study describes elderly wives of prostate cancer survivors' perspectives of adaptation to the enduring challenges of prostate cancer survival and considers their experience in the context of ethnicity. Content analysis and grounded theory methods guided data collection and analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(65 citation statements)
references
References 0 publications
0
65
0
Order By: Relevance
“…Researchers (Boehmer & Clark, 2001;Danielson et al, 1993;Dunkel-Schetter, 1984;Gotcher, 1995;Gray, Fitch, Phillips, Labrecque & Klotz, 1999;Ka'opua, Gotay, Hannum & Bunghanoy, 2005) found that supportive, caring, encouraging and positive communication is positively correlated to patient and family adjustment to cancer. Danielson et al (1993) found that it is easier if the family share their feelings versus hiding them, as this frees family members to offer each other support.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers (Boehmer & Clark, 2001;Danielson et al, 1993;Dunkel-Schetter, 1984;Gotcher, 1995;Gray, Fitch, Phillips, Labrecque & Klotz, 1999;Ka'opua, Gotay, Hannum & Bunghanoy, 2005) found that supportive, caring, encouraging and positive communication is positively correlated to patient and family adjustment to cancer. Danielson et al (1993) found that it is easier if the family share their feelings versus hiding them, as this frees family members to offer each other support.…”
Section: Discussionmentioning
confidence: 99%
“…When one's aim is to describe the couple's perspective on and experiences of prostate cancer, it is not relevant to be able to distinguish their individual experiences, but if one's aim, as in this literature review, is to discover the nature of the individual perspectives on and feelings about prostate cancer diagnosis, the participation of both partners as informants in a qualitative research project may be a problem. Ka'opua et al (2005) Challenges: Challenges: Wives were challenged by psychosocial sequelae associated with their husband's cancer treatment, thought's of life's ephemeral nature, through search for purpose and positive meaning in adversity.…”
Section: Discussionmentioning
confidence: 99%
“…On critical analysis of the 29 QRPs with regard to this issue, only six QRPs remain in which the informants could be classified distinctively as either spouse, daughter or son (inclusion criterion 3) (Green, 1987;Rosenberg, 1998;Butler et al, 2000;Giarelli et al, 2003;Ka'opua et al, 2005Ka'opua et al, , 2007. These final six 'clean' papers form the central core of this review ( Figure 1).…”
Section: Included Papersmentioning
confidence: 99%
See 2 more Smart Citations